Mass behaviour change amid COVID-19: How public health information and social norms explain the transformation - Carlini, Joan; Fry, Marie-Louise; Grace, Debra; Fox, Melissa; Zimmerman, Peta-Anne (Health marketing quarterly, 2023)
COVID-19 is a severe and ongoing threat globally, with the spread disrupting lives and society. Despite the developments of vaccines, the key measure to reduce the transmission of variants has stemmed from mass changes to personal behaviours. COVID-19 pandemic offers a unique context, where the protection behaviours enacted by an individual are necessary to keep the community safe. A social psychological perspective can be used to understand the reasons for adherence to policies and determine what other factors can shape preventive behaviours. To resolve this, in partnership with health consumers we use an online survey, with the findings substantiating preventive behaviours are positively related to COVID-19 information access and descriptive norms. Additionally, findings demonstrate the mediating role of injunctive norms on preventive behaviour suggesting that policy makers can influence decision-making by promoting health information that provides guidance on acceptable behaviours, but also demonstrates subsequent success. The integrity of the model is substantiated by partial least squares (PLS) testing.